Isolated Tricuspid Valvectomy: A Series of cases with Intravenous Drug Abuse Associated Tricuspid Valve Endocarditis - Bin Mahmood, Syed Usman; Nguemeni Tiako, Max Jordan; Mori, Makoto; Elefteriades, John A.; Bonde, Pramod; Geirsson, Arnar; Yun, James J. (The Thoracic and Cardiovascular Surgeon, 2019)
Introduction Surgical management for tricuspid valve (TV) endocarditis is usually TV repair or replacement. When repair is not feasible, and concerns for patient recidivism preclude TV replacement, tricuspid valvectomy without replacement is an option to alleviate symptoms and allow time for addiction management.Methods We reviewed our institution's experience with isolated tricuspid valvectomy for cases of intravenous drug use (IVDU)-associated endocarditis (n = 7) from 2009 to 2017.Results The decision for tricuspid valvectomy was based on each patient's comorbid condition and realization of active IVDU. This intervention resulted in 100% perioperative and mid-term survival with a mean follow-up of 25.4 months. One patient required a valve replacement in the long term only after appropriate substance abuse management was completed.Conclusion Cardiac surgeons increasingly encounter patients with active endocarditis who suffer from IVDU addiction. Drug addiction increases the risk for recurrent endocarditis and requires an effective management plan. Multidisciplinary endocarditis care teams may play a pivotal role in improving outcomes by better addressing addiction treatment.
Keywords: endocarditis; tricuspid valve; heart; valve repair